The selection and tenure of foreign ministers around the world - Bäck, Hanna 1975-; Quiroz Flores, Alejandro 1976-; Teorell, Jan 1969- (Cambridge elements, 2024)
Foreign ministers are prominent actors in foreign affairs, often second only to heads of government in their influence. Yet, despite the growing awareness of the importance of key actors, and their backgrounds, in the study of international relations, foreign ministers remain understudied. In this Element, we make an important empirical contribution by presenting an original dataset on the personal and professional background of foreign ministers, spanning thirteen countries and more than 200 years. We use these data to answer three questions: who are the foreign ministers, why are foreign ministers with particular features appointed, and why do some foreign ministers have longer tenure than others? We find that foreign ministers tend to be men of politics who are appointed both on the basis of their affinity to, and to complement the experiences of, the head of government. We also find that foreign ministers stay longer in office when they perform well or are expected to do so, but that they are more likely to lose their posts when conditions make heads of government more prone to 'pin blame' on them to deflect criticism from foreign policy failures